PENGARUH PENYUSUTAN AKTIVA TETAP TERHADAP LABA DAN PENGHEMATAN PAJAK PADA PT. KUKAR MANDIRI SHIPYARD - Kartini, Popi Surita (EKONOMIA, 2014)
PT. Kukar Mandiri Shipyard is a company which engaged in docking and shipbuilding services. Depreciation of fixed assets needs to be done because of the benefits provided and the value of the assets begin wane. Given the important role of fixed assets for the company, then it should be adjusted to the standards set by the authorities, among others: Indonesian Institute of Accountants (IAI) through the Financial Accounting Standards for Non Public Accountable Entities, the Government through the Act, and others. With the amount of fixed assets which is not small, PT.KMS must organize which depreciation method should be used in calculating depreciation of their fixed assets.The problem of this study is whether the depreciation effect on profits and can provide savings of income tax payable PT.KMS in 2012.Basic theory which used in this study is financial accounting with focus on the depreciation of tangible fixed assets, as well as the effect on earnings and saving generated income tax payable.The hypothesis is formulated as follows, depreciation of fixed assets effect on profits and can provide saving over PT.KMS income tax Payable in 2012.The method of analysis used in this study was a comparative descriptive. Based on the analysis and discussion of the result found that the earnings in 2012 using the straight-line method of depreciation Rp 4.243.411.206, declining balance provide operating loss Rp 848.475.540, and the combination of straight-line method for building and declining balance for non-construction gives profit Rp 2.601.961.264. And the combination of this depreciation method which was adjusted with tax regulations can provide savings over PT.KMS income tax payable for 2012        Rp 382.529.122 rather than the application of straight-line method. This statement gives support to the hypothesis that the depreciation of fixed assets effect on profit and can provide savings on PT.KMS income tax payable in 2012. Then the hypothesis can be accepted.